Mutluluğa Giden Bir Yol: Sakin Benlik - Sayıner, Banu (Academician Publishing Book DOI Portal, 2023)
Bu kitap, mutluluğa ulaşmanın bir yolu olarak sakin benliği ele almaktadır. Yazar, sakin benliğin ne olduğunu, nasıl elde edilebileceğini ve bu süreçte yapılması gerekenleri belirlemeyi amaçlamaktadır. Sakin benlik kavramının incelenmesi, mutluluğu sağlama yolunda destekleyici bir kişilik özelliği olarak önemlidir. Kitap, pozitif psikoloji, benlik (ego), egoizm ve gürültülü benlik gibi ilgili kavramları da içermektedir. Sakin benlik süreci, sakin benlik nitelikleri ve bu sürecin nasıl ilerlediği de ele alınmaktadır. Yazar, kitabın bilimsel alana ve insanlara katkı sağlamasını ummaktadır. This book focuses on the concept of inner peace as a way to achieve happiness. The author aims to define what inner peace is, how it can be attained, and the necessary steps to be taken during this process. The examination of the concept of inner peace is important as a supportive personality trait in the pursuit of happiness. The book also encompasses related concepts such as positive psychology, self (ego), egoism, and noisy self. The process of attaining inner peace, the qualities associated with inner peace, and the progression of this process are also discussed. The author hopes that the book will contribute to the scientific field and benefit individuals.